The Assessment of Nurse’s Performance by Using a Logbook in Hospital - Adisurya Saputra; Bahrul Ilmi; Yustan Azidin (Universitas Muhammadiyah Yogyakarta, 2019)
Background: Nurses are the majority of human resources in the hospitals whose role determines the quality of health care and they are most closely associated with patients. They are the most dominating human resources in hospital who have the most frequent interaction with the patients. Therefore, the primary indicator of the hospitals' quality service is in its nursing services. The capabilities and competencies of the nurses can be assessed through a nursing logbook strategy.Objective: This research aimed to explore the implementation of performance assessments using the nursing logbook.Method: This research was conducted using a qualitative method with a phenomenological approach. Data collection was conducted from November to December 2017 by using in-depth interviews with six participants who were selected by using purposive sampling techniques. The participants were nurses in Dr. H. Moch. Ansari Hospital. Results: The research results covered six themes, namely the existence of a nursing logbook for nurses, the purpose and the benefit of logging book in nursing, the relationship between a nursing logbook and credentials, the implementation of nursing logbook, the constraints or the barriers in the implementation of the nursing logbook, and the expectations of nurses towards the nursing logbook.Conclusion: The system of implementing the logbook as a tool for the nurses' performance assessment is not optimal due to the limited socialization to the nurses in the hospital.